Community-Acquired Pneumonia in Latin America - Iannella, Hernán A.; Luna, Carlos M. (Seminars in Respiratory and Critical Care Medicine, 2016)
Community-acquired pneumonia (CAP) is associated with significant morbidity and mortality in Latin America and the Caribbean (LAC) region. Poverty, socioeconomic factors, and malnutrition influence the incidence and outcome of CAP in LAC. In LAC, Streptococcus pneumoniae is the most frequent microorganism responsible for CAP, (incidence: 24–78%); the incidence of atypical microorganisms is similar to other regions of the world. Human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome (AIDS) is a growing problem in the LAC region, with the Caribbean being the second most affected area worldwide after Sub-Saharan Africa. Pneumococcal pneumonia remains the most common cause of CAP in HIV-infected patients, but Pneumocystis jirovecii and tuberculosis (TB) are also common in this population. The heterogeneity of the health care systems and social inequity between different countries in LAC, and even between different settings inside the same country, is a difficult issue. TB, including multidrug-resistant TB, is several times more common in South American and Central American countries compared with North America. Furthermore, hantaviruses circulating in the Americas (new world hantaviruses) generate a severe respiratory disease called hantavirus pulmonary syndrome, with an associated mortality as high as 50%. More than 30 hantaviruses have been reported in the Western Hemisphere, with more frequent cases registered in the southern cone (Argentina, Chile, Uruguay, Paraguay, Bolivia, and Brazil). Respiratory viruses (particularly influenza) remain an important cause of morbidity and mortality, particularly in the elderly. Low rates of vaccination (against influenza as well as pneumococcus) may heighten the risk of these infections in low- and middle-income countries.
Keywords: Latin America; community-acquired pneumonia; epidemiology; hantavirus